57-YEAR-OLD WOMAN WITH OESOPHAGEAL VARICES AND SUSPECTED NON- CIRRHOTIC PORTAL HYPERTENSION - Muliyanto, Jovan Amadeo; Christopher; Utami, Karina Saraswati; Margovio; Rencong, Gunady Wibowo; Susatyo, Jeffry Adijaya (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Non-cirrhotic portal hypertension (NCPH) is characterized by portal hypertension, splenomegaly, hypersplenism, and pancytopenia without histological evidence of cirrhosis. Causes include chronic infection, toxin exposure, thrombophilia, immunological disorders, and genetic abnormalities. The diagnosis of NCPH remains challenging because symptoms often mimic cirrhotic portal hypertension and access to definitive tests such as liver biopsy is limited. We report the case of a 57-year-old woman with upper gastrointestinal bleeding and oesophageal varices without clinical or radiological signs of cirrhosis. Conservative management with variceal ligation and beta-blockers was used because advanced procedures such as transjugular intrahepatic portosystemic shunt (TIPS) were not available. This case demonstrates the challenges in diagnosing and treating NCPH in resource-limited settings and the importance of supportive care and early detection.